2021
DOI: 10.1103/physrevmaterials.5.024005
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and superlattice structures of monolayer phosphorus carbide ( PxC1x )

Abstract: Phase stability and properties of two-dimensional phosphorus carbide, PxC1-x (0 ≤ ≤ 1), are investigated using the first-principles method in combination with cluster expansion and Monte Carlo simulation. Monolayer PxC1-x is found to be a phase separating system which indicates difficulty in fabricating monolayer PxC1-x or crystalline PxC1-x thin films. Nevertheless, a bottom-up design approach is used to determine the stable structures of PxC1-x of various compositions which turn out to be superlattices consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Graphite rods were used for all electrodes in a standard 3-electrode analytical setup (working, counter, and reference). Whereas many transition metals readily form metal phosphide alloys, , carbon is highly immiscible with phosphorus; , accordingly, we found graphite to be stable under cathodic conditions, displaying no significant changes in mass nor surface area under any conditions examined in this study. By comparison, the β-alumina membrane of the Na/Na + reference electrode was subject to corrosion upon prolonged exposure to the melt; as a result, it was instead used to calibrate a graphite pseudoreference electrode, the two comprising a quasireference electrode pair (Figure S5).…”
Section: Resultsmentioning
confidence: 46%
“…Graphite rods were used for all electrodes in a standard 3-electrode analytical setup (working, counter, and reference). Whereas many transition metals readily form metal phosphide alloys, , carbon is highly immiscible with phosphorus; , accordingly, we found graphite to be stable under cathodic conditions, displaying no significant changes in mass nor surface area under any conditions examined in this study. By comparison, the β-alumina membrane of the Na/Na + reference electrode was subject to corrosion upon prolonged exposure to the melt; as a result, it was instead used to calibrate a graphite pseudoreference electrode, the two comprising a quasireference electrode pair (Figure S5).…”
Section: Resultsmentioning
confidence: 46%
“…Graphite rods were used for all electrodes in a standard 3-electrode analytical setup (working, counter, and reference). Whereas many transition metals readily form metal phosphide alloys (29,30), carbon is highly immiscible with phosphorus (31,32); accordingly, we found graphite to be stable under cathodic conditions, displaying no significant changes in mass nor surface area under any conditions examined in this study. By comparison, the alumina-body Na/Na + reference electrode was subject to corrosion upon prolonged exposure to the melt, and so it was instead used to calibrate a graphite pseudoreference electrode, the two comprising a quasireference electrode pair (Fig.…”
Section: Main Textmentioning
confidence: 52%
“…In addition, a new family of 2D materials consisting of phosphorus and carbon (phosphorene carbide, (PC)) has been rather recently predicted theoretically. 40 43 Interestingly, the experimental realization of 2D PC allotropes was achieved by combining the theoretical predictions and previous experimental observations. 44 These studies demonstrated that various structures in phosphorus carbide can be produced by considering different atomic ratios of P/C.…”
Section: Introductionmentioning
confidence: 96%
“…The resulting stacks can be characterized into three types: in-plane shifted, in-plane twisted, and hybrids of the former two polymorphs. In addition, a new family of 2D materials consisting of phosphorus and carbon (phosphorene carbide, (PC)) has been rather recently predicted theoretically. Interestingly, the experimental realization of 2D PC allotropes was achieved by combining the theoretical predictions and previous experimental observations . These studies demonstrated that various structures in phosphorus carbide can be produced by considering different atomic ratios of P/C. Furthermore, structure, stability and electronic properties of PC monolayers, namely α-, β-, and γ-PC, have been predicted .…”
Section: Introductionmentioning
confidence: 99%